Resistansi Perempuan Mesir Terhadap Dominasi: Perspektif The Romance of Resistance (Lila Abu-Lughod) - Terang, Mawar Sharon; Erawan, I Ketut Putra; Mertha, Anak Agung Sagung Mirah Mahaswari Jayant (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study investigates the form of women's resistance in Egypt, when a culture of male domination motivated by patriarchy is inevitable as patrimony. Author finds that Lila Abu-Lughod's perspective through The Women of Resistance is very influential in the gradual development of Egypt women's movement mobilization. Everyday of resistance as Judith Buttler's theory in this study also able to define resistance (power) related to the element of women's vulnerability. Using the literature study method, author identifies that everyday forms of resistance are capable of giving respect to women (awareness of feminism values), trying to break the grip of the infinite power of authority possessed by men and injustice against women.